Examining the relationship between real estate and stock markets in Hong Kong and the United Kingdom through datamining - C. M. Hui, Eddie; Zuo, Wenjuan; Hu, Lun (International Journal of Strategic Property Management, 2011)
This paper aims to examine the relationship between real estate market and stock market in the United Kingdom and in Hong Kong, from 1993 to 2007, using the method of datamining. The results provide evidence for the existence of not only a positive correlation, but also a co-movement, between the two markets. Such interactions reflect the similarities among these two regions, which can be explained by two transmission mechanisms: wealth effect and credit-price effect. However, the two real estate markets respond differently upon similar adjustments of the respective stock markets. Such dissimilarity is attributed to their respective local factors. It is shown in the paper that datamining could be an appropriate option for studying this kind of relationships.First Publish Online: 14 Apr 2011